Transcervical double-balloon catheter as an alternative and salvage method for medical termination of pregnancy in midtrimester - Yi-An Tu; Chih-Ling Chen; Yen-Ling Lai; Shin-Yu Lin; Chien-Nan Lee (Elsevier, 2017)
Objective: Termination of pregnancy in midtrimester can be performed surgically or medically. The aim of this study was to evaluate the medical methods, and the additional efficacy of using a transcervical double-balloon catheter in midtrimester termination. Materials and methods: In this retrospective study, we included 167 pregnant women admitted during the period from January 1, 2011, to June 31, 2015, who were between 14 weeks and 28 weeks of gestation, and underwent intended termination of pregnancy at our center. Each of the 167 patients was allocated to either the cervical ripening balloon (CRB) group (with double-balloon catheter) or the non-CRB (without double-balloon catheter) group, by the choice or preference of the patient and her attending physician. Termination of pregnancy in the CRB group (72 patients) was conducted by placing a transcervical double-balloon catheter (COOK CRB), with both the uterine and vaginal balloons inflated with 30-80 mL of normal saline, and held in place for 12 hours, whereas in the non-CRB group (95 patients) vaginal and oral misoprostol alone were administered. Results: There were no significant differences between the CRB and non-CRB groups with regard to induction-to-delivery time (23.1 hours vs. 21.1 hours) and successful abortion rate within 30 hours (80.0% vs. 83.7%). There were no severe complications in both groups. Conclusion: There was no significant additional benefit of using a double-balloon catheter in midtrimester termination of pregnancy, although the technique was considered simple and generally well-tolerated. Placing a transcervical double-balloon catheter could be the primary method, or one of the alternative medical methods if the patient and/or obstetrician prefers no operation.